Impact of drying conditions and wet film properties on adhesion and film solidification of lithium-ion battery anodes. Issue 15 (18th November 2017) - Jaiser, Stefan; Sanchez Salach, Nicolas; Baunach, Michael; Scharfer, Philip; Schabel, Wilhelm
ABSTRACT: Electrodes constitute a vital component of lithium-ion battery cells. The property-determining, porous microstructure of anodes, which is composed of micrometer-sized graphite particles and nanoscale additives, was developed during convective removal of the solvent. In the present work, the impact of significant drying conditions and wet film properties, such as drying rate, slurry composition or active material particle size, just to name a few, is examined to provide further understanding of film solidification. The influence on both adhesion and film solidification is investigated. Subsequently, a previously developed film solidification mechanism will be critically reviewed based on findings.